PEGDA-based HistoBrick for increasing throughput of cryosectioning and immunohistochemistry in organoid and small tissue studies - Emilie Vuille-dit-Bille; Larissa Utz; Fiona E. Müllner; Valeria J. Arteaga-Moreta; Yanyan Hou; Stefan E. Spirig; Diane Ledroit-Paic; Sarah Heub; Jonas Goldowsky; Gilles Weder; Magdalena Renner (Scientific Reports)
Abstract Histology is the gold standard for analyzing tissue structure and cell morphology. Immunostaining on thin tissue sections enables precise visualization of antigens and proteins. However, for cryosectioning small tissues such as organoids, spheroids, and tumoroids there is a lack of standardized, time- and cost-effective methods, limiting the throughput of analysis. Here, we have adapted to cryosectioning our previously developed HistoBrick approach, in which small tissue arrangement is spatially controlled within arrayed mini-wells. By testing various embedding matrices, we show that an 8% PEGDA and 2.5% gelatine mixture is optimal, providing essential structural support to maintain sample integrity during cryosectioning. This embedding matrix preserves fragile substructures of human retinal organoids, which are particularly susceptible to damage during sample preparation. Using PEGDA-gelatine HistoBricks for the simultaneous embedding of 16 retinal organoids, we analyzed a time course of retinal organoid development. We observed the maintenance of photoreceptors cell bodies up to week 98 in culture, while photoreceptor outer segments were gradually lost. Further, we observed displaced photoreceptors in the region of outer segments. The PEGDA-gelatine HistoBrick is a cost-efficient tool that can be implemented for small tissue studies to increase throughput in experiments such as large-scale screenings or toxicology research.